O Património Baul e a Indústria Cultural - Marques, Sandra C. S. (Trabalhos de Antropologia e Etnologia, 2020)
Baul is a yogic philosophical and practical system that seeks to achieve the perfect state of union with the divine through continuous long-life practices (sahaja sadhana), based on transmission in a masters-disciple relationship. With at least five centuries of Bengali history, in present times, its practitioners are concentrated mainly in West Bengal, India and in Bangladesh. They are known as Baul or Fakir and primarily recognised for their musical practice of Baul songs. In 2008, “Baul songs” were inscribed on the Representative List of the Intangible Cultural Heritage of Humanity by UNESCO, following a proposal from Bangladesh. In recent years, various promotional measures and incentives for showcasing this heritage form contributed to an exponential growth of Baul media contents in Bangladesh and India as well as amongst the international public, mainly via internet, thus accelerating the transformation of Baul and Baul songs into cultural consumable goods. Many baul-fakirs argue that by detaching the songs from the baul sahaja sadhana, the songs are left with no meaning or, worst, they acquire deceptive meanings, particularly when they use a language oriented to advanced stages of knowledge. To renounce deceptive reasoning and arguing is one of the major goals of the baul system and, therefore, it is unacceptable for many baul-fakirs that their songs may be taken and said without the guidance of knowledgeable masters.